2000
DOI: 10.1161/01.hyp.36.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Thiazide-Sensitive NaCl-Cotransporter in Gitelman’s Syndrome and Primary Hypertension

Abstract: Abstract-Gitelman's syndrome is an autosomal recessive disorder characterized by electrolyte disturbances and low blood pressure. The disease is caused by homozygous or compound heterozygous inactivating mutations in the thiazidesensitive NaCl-cotransporter gene leading to reduced renal sodium reabsorption. We report 4 patients with Gitelman's syndrome from southern Sweden, all in whom we identified compound heterozygous mutations in the thiazide-sensitive NaCl-cotransporter gene (Gly439Ser, Gly731Arg, Gly741A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 23 publications
(35 reference statements)
5
61
1
3
Order By: Relevance
“…(30). It has recently been reported that TSC might interact with WNK4, which is one of the causative genes of Gordon syndrome (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…(30). It has recently been reported that TSC might interact with WNK4, which is one of the causative genes of Gordon syndrome (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of heterozygotes is approximately 1% in European populations (1), making it the most frequent inherited tubulopathy. The disease is due to loss of function mutations in the SLC12A3 gene (16q13) that codes for the thiazide-sensitive NaCl co-transporter (NCC) (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…TSC is a target of the diuretic effect of thiazides and is an established antihypertensive drug in the management of uncomplicated hypertension. Mutations in the human TSC (hTSC) gene affect blood pressure regulation, as seen in Gitelman's syndrome (Melander et al, 2000), which is a disease characterized by sodium wasting and low blood pressure. These characteristics validated the TSC gene as a logical candidate gene for hypertension susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genetic investigations have revealed several genetic variants that are candidates in the pathogenesis of hypertension (Johnson et al, 2011;Hasi et al, 2011;Fu et al, 2011). Current studies suggest that the thiazide-sensitive Na-Cl cotransporter (TSC) gene plays an important role on the risk of essential hypertension in diverse ethnic groups (Melander et al, 2000;Song et al, 2001;Glorioso et al, 2001;Matsuo et al, 2004;Zhan et al, 2007;Wang et al, 2008). The TSC gene is located on chromosome 16q13, consisting of 26 exons that encode 1021-amino acid residues (Plotkin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation